1981
DOI: 10.1210/jcem-53-1-109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyrotropin-Releasing Hormone and Metoclopramide in Patients with Phenothiazine-Induced Hyperprolactinemia*

Abstract: TRH and metoclopramide tests were performed in 10 female patients with presumed phenothiazine-induced hyperprolactinemia to define the serum PRL response to these agents. Our results show that the serum PRL response to metoclopramide is blunted in most patients with phenothiazine-induced hyperprolactinemia, and the serum PRL response to TRH is exaggerated in most patients during and 3 weeks after stopping phenothiazines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
1

Year Published

1982
1982
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…The finding that ritanserin increased the PRL response to LTP was unexpected, consequently a number of possible explanations should be considered. Several subjects exhibited increases in basal PRL levels following ritanserin and there is some evidence that elevations in basal PRL may increase the PRL response to subsequent provocative stimuli (Cowen el al., 1985;Chalmers et al, 1978;Lankford et al, 1981). In general, however, this is found with elevations in basal PRL somewhat greater than those seen here (Cowen et al, 1985;Braddock and Blake, 1981) and in addition we found no correlation between basal PRL concentration and the PRL response to LTP.…”
Section: Discussioncontrasting
confidence: 51%
“…The finding that ritanserin increased the PRL response to LTP was unexpected, consequently a number of possible explanations should be considered. Several subjects exhibited increases in basal PRL levels following ritanserin and there is some evidence that elevations in basal PRL may increase the PRL response to subsequent provocative stimuli (Cowen el al., 1985;Chalmers et al, 1978;Lankford et al, 1981). In general, however, this is found with elevations in basal PRL somewhat greater than those seen here (Cowen et al, 1985;Braddock and Blake, 1981) and in addition we found no correlation between basal PRL concentration and the PRL response to LTP.…”
Section: Discussioncontrasting
confidence: 51%
“…Although patients with PRLproducing tumor (PRL-noma) Show PRL responses to exogenous stimuli, such responses are less frequent compared to normal subjects (Tolis et al 1974;Boyd et al 1977;Crosignani et al 1977;Kleinberg et al 1977;Barbarino et al 1978;Lankford et al 1981). However, it is not clear whether there are some differences in PRL responsiveness among these patients as we have reported clear differences in Gi secretion in patients with acromegaly (Hanew et al 1980a).…”
mentioning
confidence: 80%
“…In certain circumstances these tests are of clinical importance. In phenothiazide-induced hyperpro¬ lactinaemia the Prl response to MC was blunted and that to TRH was exaggerated (Lankford et al 1981). In similar clinical conditions a blunted Prl response to TRH implies the possibility of a co¬ existing prolaetinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation of Prl secretion a single injection of thyrotrophin releas¬ ing hormone (TRH) (Jacobs et al 1971;Peillon et al 1982 (Judd et al 1976;Sowers et al 1976;Cowden et al 1979;Leroith et al 1979;Pineda et al 1979;Lankford et al 1981;Kauppila & Ylikorkala 1982) …”
mentioning
confidence: 99%